Estrategias de aprendizaje para el desarrollo de la conciencia ambiental de los niños y niñas de 5 años del nivel Inicial de Educación Básica Regular - Alva Pilco, Oswaldo (2010)
Environmental education is an essential topic these days, because it tries to preserve the environment where we are, so countries around the world have decided to adapt the international agreements and guidelines. Given this need the Peruvian government created the Ministry of Environment to channel the efforts of the State, NGOs and the Ministry of Education. The Ministry of Education has developed actions to place environmental issues as a crosscutting issue throughout the educational process and look this way awareness and educational action actors with respect to the natural environment around us. From the guidelines of the Ministry of Education guidelines, educational institutions should diversify and adapt national levels to solve environmental problems locally. Once educational institutions have worked the process of adapting national guidelines teachers should acquire, create or recreate learning strategies to develop environmental awareness of children of their institution and thus create the conditions to preserve the surrounding environment . In this regard, the strategies proposed by the Ministry of Education are games, workshops motivate processes curiosity, asking questions. Hypothesize, reading stories, drawings, etc. Therefore, this study provides some learning strategies that every teacher should know to promote environmental awareness in children five years